Beef Self-Sufficiency and Oil Palm Sustainability: Developing a Cattle-Oil Palm Integration System in Indonesia - Daeva Mubarika Raisa; Sitti Nurani Sirajuddin; Jasmal Ahmari Syamsu; Muhammad Arsyad; Lellah Rahim; Musran Munizu; Muhammad Hatta Jamil; Abd. Haris Bahrun; Abdel Razzaq Mohammad Al-Tawaha; Budiman Nohong; Siti Nurlaelah (Universitas Sebelas Maret, 2026)
The integration of cattle production with oil palm plantations is increasingly promoted in Indonesia to enhance rural economies and support community livelihoods. Achieving long-term sustainability of this system requires a clear understanding of the institutional determinants that influence the implementation across social, economic, and ecological dimensions. Therefore, this study aims to examine the institutional determinants by identifying 5 key stakeholder groups in the cattle-oil palm sectors. The location was in Tanah Bumbu Regency, South Kalimantan, which was purposively selected for cattle-oil palm integration. Primary data were collected through field observations, structured questionnaires, and in-depth interviews with 15 purposively selected experts and were triangulated using secondary reports. Interpretive structural modeling (ISM) combined with MICMAC analysis was applied to identify, structure, and classify institutional constraints. The results showed a total of 13 institutional constraints, most of which were located in the linkage and dependent quadrants, indicating high interdependence and systemic vulnerability. Major constraints included inadequate coordination, weak leadership, limited institutional capacity, as well as insufficient regulatory and financial support. ISM generated 8 hierarchical constraint levels and 5 strategic program levels, regulation, financing, interagency collaboration, extension services, and waste processing technologies emerging as key drivers of system improvement. These results underscore the need for integrated institutional strengthening to enhance SISKA performance and sustainability. As the first to apply a combined MICMAC-ISM framework to cattle-oil palm integration, this study offers a novel institutional model to facilitate evidence-based policy design and strategic program planning.